(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2024)
This work aims to analyze the case of the National Care System (SNC) in Mexico from the dimensions of the condition and position of women developed by Kate Young. To do this, we discuss the theoretical orientations and practical implications of care from a gender perspective. Then, we present the SNC proposal in its legislative scope and raise a question about its use as a tool for improving the condition and position. The reflections lead us to show that the initiatives are carried out through a vertical communication model in which women have little participation. Furthermore, they face obstacles linked to parliamentary division, economic investment, and legislative paralysis, which are fundamental in the delay or advancement of said actions. In this sense, we consider that the global health crisis derived from the Covid-19 pandemic demonstrated the urgency of generating public care policies that go beyond the abstract and address the daily needs of women so that they can improve their life projects, hence the need to include these discussions in research agendas.